Track structure of carbon ions: New measurements and simulations. (March 2020) - Conte, V.; Selva, A.; Colautti, P.
Abstract: It is recognized today that the observable radiobiological effects of ionizing radiations are strongly correlated to the local density of lesions produced in micrometer- and nanometer-sized subcellular structures, and thus to the track structure properties of interacting particles. In view of the emerging interest of carbon ions in radiotherapy, an experimental study was done for characterizing the track structure of carbon ions at different energies close to the Bragg peak. Ionization cluster size distributions for nanometer-sized target volumes were measured with the Startrack-Counter installed at the TANDEM-ALPI accelerator complex at LNL, and calculated by means of a dedicated Monte Carlo code. Measurements and simulations were performed for particle tracks crossing directly the target volume or passing nearby at specified impact parameters. Results will be presented and discussed for 12 C-ions at 6, 8, 12.5 and 20 MeV per nucleon. Highlights: New data that characterize the ionization component of the nanometric track structure of Carbon ions are presented. This new data sets may be included in a data base for codes modelling the induction of radiation damages at DNA-level. The measured nanodosimetric quantities are in good agreement with results of Monte Carlo simulations. It is possible to define an "effective volume" that takes into account the reduced sensitivity of the measuring set-up.